Verbal and More: Multimodality in Adults' and Toddlers' Spontaneous Repetitions. Issue 1 (2nd January 2023) - Soler, Marta Casla; Murillo, Eva; Nieva, Silvia; Rodríguez, Jessica; Mendez-Cabezas, Celia; Rujas, Irene
ABSTRACT: This study investigated verbal imitation from a multimodal point of view, considering the mutual influence of children's and adults' participation. Sixteen Spanish-speaking children were observed longitudinally at 21, 24, and 30 months of age in natural settings. We analyzed the multimodal characteristics of children's and adults' repetitions, considering whether they were verbal, verbal-gestural, or gestural. In addition, we also analyzed the multimodal characteristics of the utterances that were repeated (source). Measures of vocabulary and grammatical levels were also taken into account at the three points in development. Results showed that verbal-gestural repetitions were frequent in the speech of children and adults, although not as frequent as verbal repetitions. Nevertheless, verbal-gestural speech was reproduced more frequently than verbal speech. Adults were more likely to reproduce children's speech when it included gestures, which was also related to children's linguistic level. Furthermore, children and adults synchronize their multimodal communicative behaviors, coordinating the modality of their repetitions with the modality of the source speech. The results are discussed taking into account the need to study the multimodal characteristics of child-directed speech, as well as the need to study verbal repetition and multimodal communicative behaviors simultaneously, as forms of interaction that are essential to language development.